A highly adaptive directional time–frequency distribution. Issue 7 (October 2016) - Mohammadi, Mokhtar; Pouyan, Ali; Khan, Nabeel
Abstract This paper presents an automatic method of computing a high-resolution adaptive time–frequency distribution. A recently developed locally adaptive directional time–frequency distribution (ADTFD) achieves high energy concentration and cross-term suppression, but it requires manual tuning of certain parameters. One set of parameters is not applicable to all types of signals. Moreover, the ADTFD fails to achieve optimum results when a given signal has both short-duration signal components and close components. This paper overcomes the limitation of the ADTFD by locally adapting the shape of the filter. Experimental results demonstrate the efficacy of the proposed approach for a large class of signals.